The effects of land use characteristics on passenger ridership of rail-based transit oriented development in Kuala Lumpur - Bakri, Fatahsha Amira; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies, 2019)
Urbanization has been a key driver of Malaysia’s success in economic growth. Yet growing challenges in urban mobility dampen the benefits of urbanization and threaten Malaysia’s ambitions of becoming a sustainable and inclusive high-income nation. Over the years, in big cities and towns, the mobility of people has been greatly affected because of significant upsurge in the number of private vehicles on urban roads. The annual survey on morning peak travel patterns carried out by Suruhanjaya Pengangkutan Awam Darat (SPAD) reflects that the modal share of public transport (PT) in the Klang Valley region for 2013 was at 20.8% or 1.2 million of the total 5.7 million trips. Ineffective and inefficient public transportation services including limited coverage, lack of integration between public transit modes and other supporting facilities and lack of integration between land use planning and rail-based public transportation system have only exacerbated the unabated problems of chronic traffic congestion and environmental degradation (Kuala Lumpur Structure Plan 2020). The primary field survey was conducted to collect data on land use density and diversity of mixed land use within 1000m radius around the 25 selected LRT station. Whereas, the passenger volume count method was used to count the passenger ridership on weekday covering both during peak hour and off-peak hour for twelve hours duration at the 25 selected stations.The method of analysis such as content analysis and descriptive analysis were applied. The main findings from the analysis on the effects of land use density and diversity on passenger ridership show a mixed result. In order to increase the use of public transport, other main components such as park and ride facilities, feeder bus services must also be considered in the planning of transit stations.